Honey authentication: effect of irradiation and ageing on near-infrared (NIR) spectroscopy classification models - Rust, Alexandra Elizabeth (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScFoodSc)--Stellenbosch University, 2020.